The Wiley handbook of what works in child maltreatment an evidence-based approach to assessment and intervention in child protection - Dixon, Louise (Wiley-Blackwell, 2017)
"This handbook provides€an evidence-based approach to child protection-related work, and the provision of assessment and intervention services in order to maximize child well-being. It provides a comprehensive overview of contemporary research and practice that informs theory, assessment, service provision, rehabilitation and therapeutic interventions for children and families undergoing care proceedings, bringing together international knowledge from leading researchers and practitioners who draw on the evidence to inform best practice in complex family and parenting assessments as part of child care proceedings for the courts. Coverage includes the prevalence and effects of child neglect and abuse, theoretical perspectives, assessment, children’s services, and interventions with children, victims and families"--